Keefektifan Program Pendidikan Guru Sekolah Dasar - Engkoswara dkk. Engkoswara dkk. (Jurnal Ilmu Pendidikan, 2016)
The study is aimed at investigating the efectiveness of the Primary School Teacher Education Program (PGSD) in achieving its goals. Data were gathered from 12 Institutes/Faculties of Teacher Training and Education (LPTK) by using questionnaire, interview, observation, tests, and documentary study. Percentage and mean measures were applied to analyze the data. The results showed that the PGSD programs implemented since 1990 was effective, although for some PGSDs the effectiveness level is not sufficient. The insufficiency found in some PGSDs is due to shortcomings in the availability as well as the condition of program inputs and implementation processes: student, curriculum, staff and facilities, program implementation and management